2013
DOI: 10.1007/s00268-013-2143-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Oral Feeding Versus Traditional Postoperative Care After Abdominal Emergency Surgery: A Randomized Controlled Trial

Abstract: EOF was safe after abdominal emergency surgery. EOF was associated with more vomiting (treated easily and without patient discomfort) and less hunger than with TPC. No other EOF-related benefits could be demonstrated during this trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 33 publications
2
26
0
2
Order By: Relevance
“…Numerous clinical trials have provided positive evidence of the beneficial effects of FTS 3,6 . Klappenbach R, in his study on early feeding versus traditional postoperative care after abdominal surgery, found that early feeding was safe and associated with less complications and their results was comparable with those found by Boelus PG et al concluded that early feeding was associated less ileus and less anastomotic leaked in upper gastrointestinal surgery; those studies were comparable to our findings 17,18,19 .…”
Section: Discussionsupporting
confidence: 90%
“…Numerous clinical trials have provided positive evidence of the beneficial effects of FTS 3,6 . Klappenbach R, in his study on early feeding versus traditional postoperative care after abdominal surgery, found that early feeding was safe and associated with less complications and their results was comparable with those found by Boelus PG et al concluded that early feeding was associated less ileus and less anastomotic leaked in upper gastrointestinal surgery; those studies were comparable to our findings 17,18,19 .…”
Section: Discussionsupporting
confidence: 90%
“…less infectious complications and improved wound healing and immunity) (5,(11)(12)(13)15,21,22) and improved quality of life (e.g. patient satisfaction and ambulation) (12,(16)(17)(18)(19) among various surgical populations such as upper and lower gastrointestinal, obstetric and gynaecological patients. In addition, a rapid transition back to solid food is important for reducing the risk of malnutrition and its associated consequences such as infections (23) , falls (24,25) , pressure injuries (26) and morbidity and mortality (27) .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the number of days until first record of flatus or bowel opening ranged from one to nine days, and two patients were discharged with no record of flatus or stool. These results were found to be up to three days longer than previously reported for patients who were trialled with early feeding after GI surgery . Furthermore, a higher proportion of patients who developed PPOI (66%) were kept on minimal nutrition until after the first record of flatus or bowel opening, compared to patients without PPOI (53%) ( P < 0.05).…”
Section: Discussionmentioning
confidence: 60%